ASSESSMENT OF BODY MASS INDEX AND DIETARY PATTERN OF COLLEGE STUDENTS RESIDING IN RAWALPINDI AND ISLAMABAD (Journal of Medical & Health Sciences Review, 2025)
Dietary practices and nutritional status can affect a person's health in either a favorable or bad way. The major cause of the bad eating habits of college students is their sensory impressions. In order to evaluate the nutritional status and dietary habits of college students living in Rawalpindi and Islamabad, this research was conducted. The study, which involved 600 students from several institutions in twin cities, was cross-sectional. The technique of purposive sampling was used to gather data. Using a questionnaire that included demographic data, anthropometric measurements, clinical signs and symptoms, and food frequency, the respondents' nutritional status was evaluated. In order to evaluate the data, SPSS version 23.0 was used. The paired t-test was applied. The confidence interval was chosen at 95% with a significant level at p value